Metabolic Regulation of Heme Catabolism and Bilirubin Production. I. HORMONAL CONTROL OF HEPATIC HEME OXYGENASE ACTIVITY - Bakken, Arne F. (1972)
Heme oxygenase (HO), the enzyme system catalyzing the conversion of heme to bilirubin, was studied in the liver and spleen of fed, fasted, and refed rats. Fasting up to 72 hr resulted in a threefold increase in hepatic HO activity, while starvation beyond this period led to a gradual decline in enzyme activity. Refeeding of rats fasted for 48 hr depressed hepatic HO activity to basal values within 24 hr. Splenic HO was unaffected by fasting and refeeding. Hypoglycemia induced by injections of insulin or mannose was a powerful stimulator of hepatic HO. Glucose given together with the insulin abolished the stimulatory effect of the latter. Parenteral treatment with glucagon led to a twofold, and with epinephrine to a fivefold, increase of hepatic HO activity; arginine, which releases endogenous glucagon, stimulated the enzyme fivefold. These stimulatory effects of glucagon and epinephrine could be duplicated by administration of cyclic adenosine monophosphate (AMP), while thyroxine and hydroxortisone were ineffective. Nicotinic acid, which inhibits lipolysis, failed to modify the stimulatory effect of epinephrine. None of these hormones altered HO activity in the spleen. These findings demonstrate that the enzymatic mechanism involved in the formation of bilirubin from heme in the liver is stimulated by fasting, hypoglycemia, epinephrine, glucagon, and cyclic AMP. They further suggest that the enzyme stimulation produced by fasting may be mediated by glucagon released in response to hypoglycemia. The possibility is considered that the enhanced HO activity in the liver may increase hepatic heme turnover and hence, bilirubin production, which may explain the rise of unconjugated serum bilirubin observed in fasting or hypoglycemic individuals.